KONSEP ETIKA BISNIS ISLAMI - Harahap, Nurramadhani (J-MABISYA, 2020)
Islam is a perfect religion that encompasses and regulates all aspects of human life (syumul), it regulates the system of belief (tauhid), worship and also bermuamalah, where one and the other are closely interrelated. Muamalah in Islam has an adequate portion as contained in the other two dimensions. The foundation that encourages business behavior should be based not only because of fear of a government, not only because of the desire to accumulate wealth, but more than that, a businessman should rely on his behavior solely because of fear of God in trying to find favor. So that the ideal business in Islam, is a business that is able to balance rights and obligations, can create a sense of justice and fulfill the demands of virtue and nobility. Therefore, Muslim business people must submit to the axioms (basic values) of Islamic business ethics which include monotheism, balance, free will, responsibility, and truth.